Functional and intended purpose of the environmental tax in the waste management system - Biriukov, Tymur; Bukharina, Liudmyla (Management and Entrepreneurship: Trends of Development, 2023)
The article is aimed at analysis of environmental tax structure and research of its main functions’ essence. Due to the main purpose of environmental taxation, the regulatory function is defined as the major function that constitutes the ideology of environmental tax, and fiscal and social functions are considered as secondary ones.The essence and role of the environmental tax social function in the correction of socially significant negative externalities accompanying an enterprise-pollutant economic activity and influence an uninvolved third party are revealed.The dynamics and structure of environmental tax receipt to the state, local and consolidated budgets of Ukraine indicators were analyzed in order to determine its fiscal function effectiveness. The dynamics of environmental tax revenues to the consolidated budget of Ukraine by regions in order to determine those regions in which the fiscal function of environmental tax is most performed is considered.The proportion of the collected funds distribution between the levels of the budget system were studied in order to assess the effectiveness of their use for the intended purpose.The pollution volume dynamics according to the environmental tax main components were analyzed in order to assess the environmental tax regulatory functions effectiveness. The financial indicators of a representative sample of the largest environmental tax-paying enterprises were considered in order to assess the environmental tax stimulating role for the studied economic entities. The structure of budget expenditures for environmental protection measures was analyzed in order to determine the possibilities of environmental taxation compensatory goals achieving.The main problems of environmental taxation are identified and the prospects for further research are outlined.JEL Classification: E62, H23, H72, O13, Q28.